Generalized Green operator of a boundary-value problem with degenerate pulse influence - Boichuk, О. A.; Chuiko, E. V.; Chuiko, S. M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We find necessary and sufficient conditions for solvability of nonhomogeneous linear boundary-value problems for systems of ordinary differential equations with impulsive force in a general case where the number of boundary-value conditions in not equal to the order of the differential systems (Noetherian problems). We construct a generalized Greens's operator for boundary-value problems, not every solution of which can be extended from the left end point to the right end point of the interval where the solution is defined.